Factors Affecting Adolescent Out of School in Market Ambacang Kuranji District Padang City - Mardiyati, Mardiyati; Adison, Joni; Triyono, Triyono (Lembaga Riset Mutiara Akbar, 2022)
This research is based on the presence of teenagers dropping out of school. The purpose of this study is to describe: 1) Factors that affect adolescent dropouts are seen from internal factors, 2) Factors that affect adolescent dropouts are seen from external factors. This research is qualitative research. Key informants of FMM and NG students and 6 additional informants consisting of FMM's close friends and NG's close friends, FMM and NG parents, NG's sister, FMM's sister. The research instruments used in this study are interview guidelines, techniques used through data reduction, data display and data achievement. The results revealed that 1) Internal factors are lack of spirit to go to school, lack of interest in learning, always sleepy, often staying up late at night, lack of confidence in self-ability. 2) External factors that teachers are less motivated, often ridiculed for not being able to pay the obligation of school fees, the influence of friends hanging out, declining achievements and embarrassment to return to school, bullied by friends. Based on the findings of the study, it is recommended in adolescents to be able to increase their confidence and foster interest in learning